Evolutionary Story of the Low/Medium-Affinity IgG Fc Receptor Gene Cluster - Lejeune, Julien; Brachet, Guillaume; Watier, Hervé (Frontiers in Immunology, 2019)
Low/intermediate affinity Fc-gamma receptors (FcγR) are crucial for the recognition of immune complexes and IgG-sensitized microorganisms by phagocytic and cytotoxic effector cells. In all mammalian species studied so far, their genes are clustered in a single locus. However, this locus differs between humans and mice, both in the number of genes and the structure/function of the encoded receptors. We show that murine fcgr3 evolved through several steps into FCGR2A, its ortholog, which is specific to primates. One of these steps was the insertion of a retroviral element bringing a new intracellular exon comprising a non-canonical ITAM motif. We also show that the fcgr3-hspa6-fcgr4-fcgr2b module in mammals that has evolved in a FCGR2A-HSPA6-FCGR4-FCGR2B module in primates, was subsequently duplicated in apes through a Non-Allelic Homologous Recombination (NAHR), giving birth to FCGR2C, a hybrid gene between FCGR2B and FCGR2A. The FCGR4 duplication, which occurred simultaneously, eventually resulted in the emergence of FCGR3B, while FCGR3A remained the true FCGR4 ortholog. FCGR2C and FCGR3B, markers of this NAHR, are present in gorillas and chimpanzees, whereas they are absent in orangutans and more distant primates, such as gibbons and macaques. These data need to be taken into account when testing IgG-based therapies in animal species.